The Risk of Postpartum Hemorrhage Following Prior Prelabor Cesarean Delivery Stratified by Abnormal Placentation: A Multicenter Historical Cohort Study - Shilei, Bi; Lizi, Zhang; Yulian, Li; Yingyu, Liang; Lijun, Huang; Minshan, Huang; Baoying, Huang; Jinping, Jia; Yinli, Cao; Shaoshuai, Wang; Xiaoyan, Xu; Ling, Feng; et al. (Frontiers in Medicine, 2021)
Introduction: Prior pre-labor cesarean delivery was associated with increasing the risk of previa in a second delivery, whether it may impact postpartum hemorrhage independent of abnormal placentation. This study aimed to assess the risk of postpartum hemorrhage (PPH) stratified by abnormal placentation following a first cesarean delivery (CD) before the onset of labor (pre-labor) or intrapartum CD. Materials and Methods: This multicenter, historical cohort study involved singleton pregnant women at 28 weeks gestation or greater with a CD history between January 2017 and December 2017, in eleven public tertiary hospitals within seven provinces of China. PPH was analyzed in the subsequent pregnancy between women with prior pre-labor CD and women with intrapartum CD. Furthermore, postpartum hemorrhage was analyzed in pregnant women stratified by complications with placenta previa (PP) alone (without placenta accreta spectrum disorders [PAS]), complications with PP and PAS, complications with PAS alone (without PP), and normal placentation. We performed multivariate logistic regression to calculate adjusted odds ratios (aOR) and 95% confidence intervals (CI), controlling for predefined covariates. Results: Of 10 833 pregnant women, 1197 (11%) had a history of intrapartum CD and 9636 (89%) had a history of pre-labor CD. Prior pre-labor CD increased the risk of PP (aOR 1.91, 95%CI 1.40-2.60), PAS (aOR 1.68, 95%CI 1.11-2.24), and PPH (aOR 1.33, 95%CI 1.02-1.75) in subsequent pregnancy. After stratification by complications with PP alone, PP and PAS, PAS alone, and normal placentation, prior pre-labor CD only increased the risk of PPH (aOR 3.34, 95%CI 1.35-8.23) in subsequent pregnancy complicated with PP and PAS. Conclusions: Compared to intrapartum CD, prior pre-labor CD increased the risk of PPH in a subsequent pregnancy only when complicated by PP and PAS.